Origins and early evolution of arthropods. (18th March 2014) - Edgecombe, Gregory D.; Legg, David A.; Smith, Andrew
Abstract Phylogenomics reconstructs an arthropod tree in which a monophyletic Arthropoda splits into Pycnogonida + Euchelicerata and Myriapoda + Pancrustacea. The same chelicerate–mandibulate groups are retrieved with morphological data sets, including those encompassing most taxa known from Palaeozoic Konservat‐Lagerstätten. With respect to the interrelationships of the three extant clades of Panarthropoda, a sister group relationship between Onychophora and Arthropoda is endorsed by transcriptomics and microRNAs, although this hypothesis forces homoplasy in characters of the segmental ganglia that are shared by tardigrades and arthropods. Cambrian lobopodians, dinocaridids, bivalved arthropods and fuxianhuiids document the successive appearance of characteristic arthropod features in the stem lineage of Euarthropoda (crown‐group arthropods). Molecular dating suggests that arthropods had their origin and initial diversification in the Ediacaran, but no convincing palaeontological evidence for Panarthropoda is available until the earliest Cambrian.